An investigation of the number of inserts effect on the machining time and metal removal rate during the milling of AISI D3 steel at high cutting speeds - Dilipak, Hakan (Strojniški vestnik, 2009)
In this study, the effect of the number of milling cutter inserts on the metal removal and the machining time in milling of AISI D3 cold work tool steel has been investigated. A CNC machining centre was used for cutting operations. The machinability tests were carried out in dry cutting conditionsat various cutting speeds, feed rates and with different number of inserts. The flank wear was measured by using an optical microscope in order to determine the tool life. The machining time decreased when the cutting speed, the number of inserts and feed rate increased. On the contrary, the flank wear increased when the same parameters increased. The flank wear increased gradually until the first 0.2 mm, but the wear rate increased significantly when above this point under different cutting conditions and with different numbers of inserts. This condition following the first 0.2 mm wear value was constant due to the high cutting speed rates based on the notch wear which emerged from fast wear.
Keywords: rezkanje; orodna jekla; obraba; hitrost; čas